2008
DOI: 10.1186/1757-1626-1-87
|View full text |Cite
|
Sign up to set email alerts
|

Successful removal of a giant intrathoracic lipoma: a case report and review of the literature

Abstract: We report a case of a 44-year old female who presented to her physician complaining of mild dyspnea. A follow-up chest X-ray and chest computed tomography scan revealed a giant bilateral intrathoracic mass, filling the right thoracic cavity and extending across the anterior mediastinum into the left chest cavity. This large mass caused a marked shift in the midline structures, displacing the heart to the left hemi-thorax. The patient underwent surgical removal of the thoracic and breast mass, with histologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Therefore, although lipoma is histologically diagnosed as a benign tumor and grows slowly, those growing and causing clinical symptoms should be considered clinically malignant and subjected to surgical procedures for complete removal. Lipomas that increase in size may undergo transformation to liposarcomas although they rarely metastasize 4 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although lipoma is histologically diagnosed as a benign tumor and grows slowly, those growing and causing clinical symptoms should be considered clinically malignant and subjected to surgical procedures for complete removal. Lipomas that increase in size may undergo transformation to liposarcomas although they rarely metastasize 4 …”
Section: Discussionmentioning
confidence: 99%
“…Lipo sarcomas have attenuation coefficients of higher than -50 Hounsfield units [7]. Histologically, pleural and intrathoracic lipomas contain abundant mature adipose tissue with no mitotic activity, with normal fibro-connective tissue in between but sometimes may contain foci of calcification and fat necrosis especially in large tumors [8]. Lipo sarcomas, on the other hand, have adipose Cells of varying size with hyperchromatic nuclei and eosinophilic cytoplasm.…”
Section: Investigationsmentioning
confidence: 99%
“…Lipo sarcomas, on the other hand, have adipose Cells of varying size with hyperchromatic nuclei and eosinophilic cytoplasm. Liposarcomas can also have mitoses associated with multinucleated histiocytes and fatty necrosis seen in 25% of cases [8,9]. SFTP is a rare, usually benign and indolent growing tumor that accounts for approximately 5% of all pleural neoplasms [10].…”
Section: Investigationsmentioning
confidence: 99%
“…The density is often not uniform because lipoma frequently contain fibrous stroma. Ramona et al [13] reported a case in which CT revealed several areas of dystrophic ring type calcifications within a field of scattered dense soft tissue elements.…”
Section: Ijsrnetmentioning
confidence: 99%